Out‐of‐range INR results lead to increased health‐care utilization in four large anticoagulation clinics - Barnes, Geoffrey D (Res Pract Thromb Haemost, 2018)
BACKGROUND: The impact on health‐care costs and utilization of a single out‐of‐range (OOR) INR value not associated with bleeding or thromboembolic complication among chronic warfarin‐treated patients is not well described. METHODS: At four large phone‐based anticoagulation clinics (total 14 948 patients), warfarin‐treated patients with atrial fibrillation (AF) or venous thromboembolism were retrospectively propensity matched into an OOR INR group (n = 116) and a control group (n = 58). Types and frequency of contacts (eg, phone, voicemail, facsimile) and personnel involved were identified. A prospective time study analysis of 59 OOR and 92 control patients was performed over 8.5 days to record the time required to care for these patients. 2016 USD cost estimates were generated from average salaries. RESULTS: OOR and in‐range INR patients experienced an average of 4.2 and 3.2 (P < .001) INR lab draws until two sequential tests were in range. OOR INR patients required an average of 5.3 interactions with the anticoagulation clinic vs 3.7 for in‐range INR patients (P < .001). OOR INR patients more often required phone calls, fewer mailed letters, and more often required multiple types of contact than in‐range INR patients. In the prospective analysis, total median time involved for each OOR INR value was 5.1 minutes (IQR 3.7‐9.5) vs 2.9 minutes (IQR 1.8‐5.8) for control INR values (P < .001). At the clinic level, OOR INR values were associated with a yearly staff cost of $17 938 (IQR $8969‐$31 391). CONCLUSIONS: We quantified the amount of extra anticoagulation staff effort required to manage warfarin‐treated patients who experience a single OOR INR value without bleeding or thromboembolic complications, which leads to higher healthcare utilization costs.